Village Development: Effect of Vilage Fund and Village Head Education - Anggun Nadia; Benedictus Raksaka Mahi (Economics Development Analysis Journal, 2023)
Village Autonomy allows villages to realize more advanced and prosperous rural development. According to some literature, village development needs sufficient funds. In Indonesia, Village Fund has become one of the necessary funds for villages since 2015. Besides the effect of the Village Fund amount, this study evaluates the role of village leaders in optimizing Village Fund management. This study aims to analyze the impact of village head education support in managing the Village Fund on the development of village status in Indonesia empirically. The analytical method uses cross-sectional multiple linear regression in the data between 2018 and 2020. This study uses changes in the village building index (IDM) score to reflect the development of village status each year as the dependent variable, then Village Fund and interaction between Village Fund and Village Head education as the independent variables. The results denote that the management of the Village Fund will be more effective in influencing the growth of village development if the village has a village head with an education above high school. Therefore, the Central Government should provide intervention on the policy criteria for allocating Village Funds, especially performance allocation, by including village head education as an additional indicator in the Village Fund management process.